Chitosan-based hybrid materials as adsorbents for textile dyes–A review. (September 2020) - Qamar, Sarmad Ahmad; Ashiq, Mehvish; Jahangeer, Muhammad; Riasat, Areej; Bilal, Muhammad
Abstract: Chitosan is a pseudo-natural cationic polysaccharide in nature. Because of its wide range of physical and biochemical properties, chitosan and its hybrid materials are being used in various industrial sectors. The dyes and other industrial effluents extensively compromise the plant growth and affect the food chain, these substances may also induce toxicity, mutagenicity, and carcinogenicity. Textile dyes affect the quality of water bodies, impair photosynthesis, and increase biochemical and chemical oxygen demand (BOD and COD). Removal of dyes must be performed by either physicochemical, phyto-remediation, and/or biobased methodologies. All these types of dyes degradation methodologies possess various drawbacks. Therefore, attention towards chitosan and modified chitosan-based materials has been devoted in the previous few decades due to its biocompatibility, biodegradability, less-toxic, and eco-friendly nature. However, its attractive properties rely on its ability to form linkages with the sulfonic groups of anionic dyes by the electrostatic force of attraction and adsorption of dyes effluents and other heavy metals in various capacities. This review highlights the properties and modifications of chitosan via (i) crosslinking; (ii) graft copolymerization and, (iii) surfactant impregnation for the development of chitosan-based hybrid materials with improved dye sorption properties have been described. In addition, chitosan nanostructures that are being studied for the smart degradation of textile dyes and effluents have also been discussed. This review provides an insight into the chitosan-based adsorbents and encourage researchers to use chitosan-based composites/blends for the removal of a variety of different dyes and dye-based effluents.